Formulation development, characterization, and evaluation of sorafenib-loaded PLGA-chitosan nanoparticles - Abdul Mateen; Abad Khan; Ismail Khan; Lateef Ahmad; Amjad Khan; Abdul Salam (Frontiers Media S.A., 2024)
The basic purpose of this work was to develop environmentally friendly, biodegradable, and biocompatible polymeric nanoparticles of sorafenib that can effectively release the desired drug in a customized and controlled manner for targeting hepatocellular carcinoma. The solvent evaporation technique was employed for the synthesis of sorafenib-loaded PLGA-chitosan nanoparticles, followed by various experimental specifications and compatibility studies using poloxamer 407 as the stabilizer. The best nanoparticles thus synthesized were selected to be used for cytotoxicity investigations through in vitro and in vivo assessments. For the in vitro drug release tests, the dialysis bag diffusion technique was used. For both chitosan nanoparticles and PLGA loaded with sorafenib, a biphasic release pattern was found, exhibiting a protracted release lasting 10 days after a 24-h burst release. As experimental animals, rabbits were utilized to evaluate different in vivo pharmacokinetic properties of the selected formulations. Plasma samples were extracted with acetonitrile and analyzed through the developed HPLC method. Pharmacokinetic parameters such as AUC0-t, Cmax MRT, Vd, and half-life (t1/2) were enhanced significantly (p ≤ 0.001), while clearance was considerably decreased (p ≤ 0.001) for the chosen synthesized nanoparticles in contrast to the commercially accessible sorafenib formulation (Nexavar®). The cytotoxicity of the reference drug and sorafenib-loaded PLGA and chitosan nanoparticles was calculated by performing an MTT assay against HepG2 cell lines. The developed polymeric sorafenib nanoformulations possess the appropriate physicochemical properties, better targeting, surface morphology, and prolonged release kinetics. The pharmacokinetic parameters were improved significantly when the results were compared with commercially available sorafenib formulations.